Determinantes da reserva de caixa das empresas brasileiras - Carracedo, Andre Chamadoira (2010)
Studies that investigate the reasons about the cash holdings are gain importance around academicals and still are in early stage, according to global academic research. Additionally, empirical studies have found significant high levels of cash holdings among international companies. We found three theories that support academic explanation of the determinants of the cash holdings: tradeoff theory, pecking order theory and agency theory. This study has the purpose to investigate empirically the determinants of the cash holdings among Brazilian companies, as well investigate the existence of a pro-active cash management policy. We use panel data to evaluate 198 Brazilian companies, between 1998 and 2008, according to Economatica source of data. The evidences lead us to conclude that cash management is an important decision to be made in corporate level. Theories support the explanation of the determinants in a complementary way.